Evaluation of surface roughness of composite according to surface treatment - Sabah A Ismail (University of Mosul, College of Dentistry, 2005)
Abstract The purpose of this study was to evaluate the effect of various finishing and polishing procedures on the surface roughness (Ra) of two composite resins: An organically modified ceramic (Definite) and a micro hybrid (Tetric). Thirty specimens of each composite resin were fabricated using a stainless steel mold of 5 mm in diameter and 2 mm in depth. The composite resin was covered by a Mylar strip and pressed flat with a microscopic glass slide and light cured. The specimens for each composite resin were divided into three groups, each of ten. The specimens in group one received no treatment, while the specimens in group two and three were finished with diamond bur. After finishing with diamond burs group three were polished with Sof-Lex discs. The surface profile of the specimens was obtained with a surface profile-testing machine (Profilometer). The roughness value in micrometer (μm) was recorded as the average Ra. Results showed higher surface roughness in groups finished with diamond burs followed by groups finished with diamond burs and polished with Sof-Lex discs while groups set against Mylar strip showed the lowest roughness values. The result revealed no significant difference in surface roughness values between the two composite resins.